Parallelism of multi-scale quantum harmonic oscillator algorithm - Yan HUANG; Peng WANG; Kun CHENG; Feng LIU (Tongxin Xuebao, 2016)
MQHOA was a novel intelligent algorithm constructed by quantum harmonic oscillator's wave function.Sampling was the basic operation and main computational burden of MQHOA.The independence of sampling operation constructs MAHOA’s parallelism.Parallel granularity was obtained by experiments of group parameter and sampling parameter,and MQHOA-P was proposed.Experiments were done in a cluster of ten nodes on six standard test functions.By changing node number,function dimension and sampling parameter,experiments of MQHOA-P’s speed-up ratio were done.The experimental results show the good performance of MQHOA-P’s speed-up ratio and expansibility.MQHOA-P can be deployed and run on multiple nodes in a large-scale cluster.